Influence of the side step under unpredictable conditions on lower limb and trunk kinematics of lateral cutting maneuvers in basketball players - Kameda, M.; Mizutani, M.; Sugiyama, T.; Kiba, K.; Maeda, A. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The present study compared the kinematics of lower limb and trunk motion in lateral cutting maneuvers (180° turn) during side steps under preplanned (PRE) and unpredictable (UN) conditions in defensive basketball players. The participants were 14 players from a college female basketball team who were instructed to view an arrow directed either to the right or the left on a monitor in front of them while moving with side steps toward the right. When a right-directed arrow was provided, they side-stepped 3 m by to the right, whereas a leftdirected arrow prompted them to move 3 m to the right, perform lateral cutting to the left, and to move back to the starting spot with a side step. Trials were performed under 2 conditions: 1) PRE condition: Participants were informed about the direction of the arrow signal beforehand. 2) UN condition: Participants responded to a randomly presented direction of the arrow signal. Kinematic parameters and ground reaction force (GRF) data were collected using an optical three-dimensional motion analysis system at 300 Hz and a force plate at 1500 Hz. The data only in the lateral cutting trials were analyzed from the instant of foot strike on the force plate to the instant of toe-off during lateral cutting. The results showed that the 3-m side step shuttle time and foot contact time during lateral cutting in UN were longer than those in PRE. The horizontal component of the maximal GRF and the impulse during lateral cutting in UN were larger than those in PRE. The center of gravity (CG) lateral velocity toward the right at the cutting step foot strike was higher in UN than in PRE. In UN, the right lower limb and trunk were inclined less to the left than in PRE. The present results show that, in UN, the participants were unable to reduce their lateral velocity before the cutting step and that their right lower limb and trunk at the cutting step (middle phase) were inclined relatively to the right, thus increasing the degree of movement of their CG to the right. Therefore, the participants needed some time to move their CG back to the left, which prolonged the contact time and thus the time taken for the 3-m side step shuttle movement in UN.